At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
It looks like a quadratic equation, so move everything to one side using inverse operations and factor.
you probably want to start with \[x^2-6x=-3\] and then complete the square otherwise start with \[x^2-6x+3=0\] and use the quadratic formula because \(6\) is even, completing the square is probably easiest do you know how to do that?
Or complete the square.....
if you use the quadratic formula then a=1 b= -6 c= 3
you need to get x by its self so minus it from both sides and you get -4x=-3 and divide both sides to get x by itsself so you answer is x=1
hope i helped:)
actually 1 is not the answer
oh wait yeah sorry i messed up
if you start with \[x^2-6x=-3\] then take half of 6, which is 3, square it to get 9 and then write \[(x-3)^2=-3+9=6\] take the square root, don't forget the \(\pm\) and get \[x-3=\pm\sqrt6\] then add 3 to both sides and you are done
I had gotten stuck on this part x^2 - 6x +3 = 0
Quadratic formula is: x = [-b +-sqroot(b² - 4*a*c)] / 2a
I got x = 10.9 or x = -1.1 is it wrong?
\[x=3\pm\sqrt6\] is the correct answer
yeah satellite73 is correct I messed up
@jbarreto17 Do not estimate the square root unless the question specifically asks you to.